Efektivitas Intensitas Event Marketing LINE Webtoon dan Terpaan Iklan Produk pada akun Instagram @linewebtoon.id dalam Keputusan Pembelian Koin di LINE Webtoon - Andina Mutiara Insan; Hedi Pudjo Santosa; Amida Yusriana (Interaksi Online, 2021)
LINE Webtoon carries out various promotions to promote its products and with a fairly frequent intensity, one of the promotions includes event marketing and organic product Ads on Instagram. When compared to U.S and Taiwan webtoons, the events they do are not more frequent and not more numerous than those held in Indonesia. Furthermore, U.S and Taiwan webtoons also very rarely advertise their comic products organically on Instagram accounts. However, in reality, the number of paid episode readers on LINE Webtoon Indonesia is unstable when compared to other countries, the U.S. and Taiwan webtoons have more stable paid episode readers. This study aims to determine the effectiveness of the intensity of LINE Webtoon's marketing events and exposure to product advertisements on the @linewebtoon.id Instagram account in the decision to purchase coins on LINE Webtoon. The theory used in this research is the Elaboration Likelihood Model and Strong Advertising Theory. To determine the sample, this study uses a non-probability sampling technique. The sample consisted of 50 females and males, aged 18-25 years who used LINE Webtoon, followed the @linewebtoon.id Instagram account, and purchased coins on LINE Webtoon in the last 6 months. The results show that the effectiveness of event marketing intensity in purchasing decisions has a significance value of 0.015 which can be interpreted as significant, a correlation coefficient of 0.251 which means that it has a weak closeness and this correlation test has a positive relationship direction. Furthermore, the effectiveness of product advertising exposure in purchasing decisions has a significance value of 0.440 which can be interpreted as insignificant